Effect of pyridine and its derivatives on the corrosion of 70/30 brass in 1% H2SO4 solution - Gupta P.; Chaudhary R.S.; Namboodhiri T.K.G.; Prakash B. (My University, 2025)
The inhibitive action of Pyridine and some of its derivatives (2-, 3-, and 4-Picoline) towards the corrosion of 70/30 brass in 1% H2S04 solution has been investigated. Weight loss, solution analysis and potentiostatic polarisation studies were carried out in 1% H2SO4 with various concentrations ofthefour inhibitors. All the compounds except 3-Picoline werefound to act as mixed inhibitors and allfour compounds obey the Langmuir adsorption isotherm up to their optimum concentrations. The inhibitive efficiency of these compounds may be arranged in the following order: 2-Picoline > 4-Picoline > 3-Picoline > Pyridine. The influence of the substituent -CH3 group in the Pyridine ring is explained on the basis of molecular structure. © 1982 Maney Publishing.